PENGARUH KOMPETENSI GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA ( Studi di SMP Negeri Sub Rayon 05 Kota Semarang ) - 11.52.02.0155, Nuril Zubaidah (Jurnal Mahasiswa Pasca Sarjana, 2013)
Research objectives: 1) The effect of teacher competence on job satisfaction, 2) effect of teacher competence on teacher performance, 3) The effect of work motivation on job satisfaction, 4) The effect of work motivation on performance, 5) The effect of job satisfaction on performance, 6) Analyze satisfaction mediate the competence of teachers working on teacher performance, 7) Analyze job satisfaction mediates the motivation to work on the performance of teachers.The population in this study 161 teachers of SMP 05 Semarang Sub Rayon. and use the sample questionnaires and questionnaires. Methods of processing and analyzing data using descriptive and multiple linear regression with SPSS 20The results prove that 1) the competence of teachers and a significant positive effect on job satisfaction with great influence 40.2%, 2) There is a significant effect between the competence of teachers on teacher performance by 65.6%, 3) There is a significant effect between work motivation on job satisfaction is at 38.8%, 4) There is a significant effect between work motivation on the performance of 41.9%, 5) There is a significant effect between job satisfaction on performance that is equal to 57.8%, 6) does not prove that mediating role of job satisfaction job motivation on teacher performance Keywords: Teacher Competence, Work Motivation, Teacher Performance, Mediation Job Satisfaction